The India Museum Revisited - MacGregor, Arthur (UCL Press, 2023)
The museum of the East India Company formed, for a large part of the nineteenth century, one of the sights of London. In recent years, little has been remembered of it beyond its mere existence, while an assumed negative role has been widely attributed to it on the basis of its position at the heart of one of Britain's arch-colonialist enterprises. Extensively illustrated, The India Museum Revisited provides a full examination of the museum's founding manifesto and evolving ambitions. It surveys the contents of its multi-faceted collections - with respect to materials, their manufacture and original functions on the Indian sub-continent - as well as the collectors who gathered them and the manner in which they were mobilized to various ends within the museum. From this integrated treatment of documentary and material sources, a more accurate, rounded and nuanced picture emerges of an institution that contributed in major ways, over a period of 80 years, to the representation of India for a European audience, not only in Britain but through the museum's involvement in the international exposition movement to audiences on the continent and beyond.